Isolation, identification and comparative genomic analysis of Lactobacillus salivarius from Mongolian horse vagina - Zhao, Yiping; Liu, Yuanyi; Tao, Jinshan; Cao, Jialong; Lin, Yanan; He, Qianqian; Fang, Xinlan; Yun, Siqin; Du, Ming; Su, Shaofeng; Bao, Tugeqin; Bai, Dongyi; et al. (Frontiers in Microbiology, 2025)
IntroductionReproductive health in mares is pivotal for the sustainability of the equine industry, yet vaginal microbiota dysbiosis remains an underrecognized contributor to infections such as endometritis and bacterial vaginosis. While Lactobacillus spp. dominate healthy vaginal ecosystems in humans and livestock, their role in equine reproductive health, particularly in resilient breeds like Mongolian mares, is poorly understood. This study aimed to isolate and characterize a novel Lactobacillus strain from the vaginal microbiota of healthy Mongolian mares and evaluate its probiotic potential for mitigating equine reproductive disorders.MethodsA polyphasic approach integrating phenotypic, biochemical, and 16S rRNA gene sequencing was employed to isolate and identify a novel Lactobacillus salivarius strain (Y20) from the vaginal microbiota of healthy Mongolian mares. The probiotic potential of Y20 was assessed through in vitro assays, including tolerance to low pH (pH 2.5) and bile salts (0.3%), antagonistic activity against equine pathogens (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa), and antioxidant capacity (DPPH radical scavenging assay). Whole-genome sequencing (1.74 Mb, 33.01% GC content) was performed to analyze genes related to carbohydrate metabolism, adhesion factors, bacteriocin biosynthesis, and stress response pathways. Comparative genomics was used to explore phylogenetic relationships and genomic adaptations for vaginal colonization.ResultsLactobacillus salivarius Y20 demonstrated robust tolerance to low pH and bile salts, potent antagonistic activity against key equine pathogens, and significant antioxidant capacity (82.4% DPPH radical scavenging). Genomic analysis revealed genes encoding carbohydrate metabolism, adhesion factors, bacteriocin biosynthesis (including a novel putative bacteriocin cluster), and stress response pathways. Comparative genomics confirmed Y20’s close phylogenetic relationship with horse-derived Lactobacillus salivarius strains and identified unique genomic adaptations for vaginal colonization.DiscussionThese findings identify Lactobacillus salivarius Y20 as a promising candidate probiotic for mitigating equine reproductive disorders. Its multifaceted probiotic properties, including pathogen inhibition, antioxidant activity, and genomic adaptations for vaginal colonization, suggest potential applications in sustainable equine health management. This study advances microbiome-based strategies as viable alternatives to antibiotics, offering new avenues for improving reproductive health in mares.